Evaluation of the Adoption of World Health Organization 10-Group Classification System for Cesarean Section in Egyptian Hospitals - Dewedar, Reham (AUC Knowledge Fountain, 2025)
Egypt has seen a significant rise in Cesarean Section (CS) deliveries over the past decade. While CS is a crucial procedure that can save lives when medically indicated, its misuse poses risks to both mothers and infants, including potential mortality. To address this issue, the WHO introduced the 10-Group Classification System (TGCS) in 2015 to standardize CS monitoring, aiming to prevent overuse or underuse of CS and to enable comparisons across health facilities and countries. This tool was introduced in Egypt through a training session conducted by the World Health Organization (WHO) in 2021.This study examines the effectiveness of this WHO TGCS training. Eighteen obstetrics and gynecology practitioners from university and government hospitals across seven governorates in Upper Egypt, who had taken the training, were interviewed by phone. Interview questions addressed knowledge and implementation of the TGCS, as well as attitudes toward CS. The study revealed that while the WHO TGCS training effectively introduced the classification system, its application was limited. Only half of the participants implemented the system in their practice, and there was a noticeable lack of institutionalization of the tool. Additionally, more than half reported no official audit procedures in their hospitals. Despite medical professionals' general preference for vaginal delivery due to the risks and recovery associated with CS, elective or unnecessary cesarean sections still occurred, reflecting a discrepancy between practice and consensus. These results suggest that to enhance the effectiveness of TGCS training, and ensure sustained application of acquired knowledge, there should be institutional endorsement of the TGCS within hospital policies and protocols. Furthermore, a comprehensive national strategy is needed, focusing on the formal integration of TGCS in hospitals, and providing adequate allocation of financial, human, and technological resources to support the effective application of training in clinical settings.